Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kualitas Tidur Selama Melakukan Senam Hamil Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu - Monikaliza Monikaliza; Ronalen Br. Situmorangi; Danur Azissah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
According to the World Health Organisation (WHO) (2025), maternal health disorders remain a global problem, with a maternal mortality ratio of 197 per 100,000 live births influenced by physical and psychological conditions during pregnancy. Sleep disorders are a common complaint among pregnant women and can affect the health of both mother and foetus. Data from the Bengkulu City Health Office in 2024 shows that there were 428 pregnant women in the working area of the Sawah Lebar Community Health Centre. This study aims to determine the relationship between the knowledge and attitudes of pregnant women and their sleep quality while doing pregnancy exercises in the working area of the Sawah Lebar Community Health Centre in Bengkulu City in 2025.This study uses a correlational analytical method with a cross-sectional design. Data collection was conducted using questionnaires administered to 45 pregnant women using purposive sampling. Data analysis was performed using the Chi-Square test (p-value < 0.05).The results showed that most respondents had good knowledge (60%), supportive attitudes towards pregnancy exercises (66.7%), and good sleep quality (68.9%). Bivariate analysis showed a significant relationship between pregnant women's knowledge and sleep quality during pregnancy exercise (p-value = 0.000), while pregnant women's attitudes did not show a significant relationship (p-value = 0.000).This study shows that pregnant women's knowledge and attitudes are significantly related to sleep quality during pregnancy exercise. The results of this study are expected to serve as a basis for improving pregnancy exercise education by health workers and as a reference for further research.